Perusahaan Tidak Adil kepada Saya!: Gambaran Perceived Justice pada Situasi Perubahan - Vera Elisabeth; Rayini Dahesihsari (Psympathic : Jurnal Ilmiah Psikologi, 2017)
Employees perceive the fairness of organization’s systems and procedure is called perceived justice. Some studies indicated that perceived justice affects many organizational attitudes and behaviors, such as job satisfaction, absenteeism, counterproductive behavior, and turnover. Therefore, organization needs to give attention on employees’ perceived justice. This study was taken in PT. EFG, where its employees have been complaining about  many changes happened. This study was conducted with mixed method approach. Quantiative data was collected through 114 online questionnaires. The questionnaire measures three dimensions which are distributive justice, procedural justice, and interactional justice. Qualitative data was collected through interview to five participants with high and low intensity of perceived justice. The findings show that supervisor play an important role in  determining other employees’ procedural and interactional justice. Other factors such as characteristics, previous experiences, perception about change and coworkers also affect employees’ perceived justice.